Penatalaksanaan Skabies Infeksi Sekunder Pada Anak Usia Sekolah Dengan Pendekatan Kedokteran Keluarga Di Puskesmas Natar - Aprina Adha Widiastini; Fitria Saftarina (MAJORITY, 2020)
Scabies is a parasitic infection of the skin caused by Sarcoptes scabei var hominis. Synonyms or other names for scabies are scabies, the itch, gudig, budukan, and agogo itching. Many factors support the development of this disease, including low socioeconomic conditions, poor personal hygiene, level of knowledge, age and contact with sufferers both directly and indirectly. This situation facilitates the transmission and infestation of Sarcoptes scabei. This study is a case report. Primary data were obtained through history taking, physical examination and home visits. Assessment is based on a holistic diagnosis from the beginning, process, and end of the study quantitatively and qualitatively. In the results obtained a 7-year-old boy with complaints arise pimples accompanied by itching, especially at night since 11 months ago. Patients have aspects of internal risk in the form of poor personal hygiene, habits of children who sleep in the same room with their parents, bed linen, pillowcases, and curtains are rarely washed, repeated use of clothes before washing and use towels together. The external risk aspects are low income family with a fairly dense home environment, lack of cleanliness of the home environment, and low patient and family knowledge about scabies. Home visits were carried out 3 times to intervene in patients and families. The diagnosis and management of these patients is done holistically, patient centered, family approached and based on several theories and the latest research. In the process of behavior change, An. M has reached the trial stage. The process of behavior change in An. M and family in personal hygiene have been seen after intervention.